Crow and Raven in Lithuanian and Slavic Phraseology and Ethnic Culture - Plachovičiūtė, Diana (Slavistica Vilnensis, 2023)
The aim of the article is to explore whether the image of the crow and raven in Lithuanian phraseology and ethnic culture is similar to that of its Slavic neighbors or exhibits distinctive characteristics. The research material includes phraseological units in Lithuanian, Polish, Belarusian, and Russian with the components crow and raven. The analysis encompasses phraseologisms found in both vernacular and literary sources, applying the theory of conventional figurative language and the comparative method. Special attention is given to the portrayal of crows and ravens in folklore and folk beliefs. The findings reveal a predominantly negative perception of both birds in Lithuanian and Slavic phraseology and ethnic culture. The main features of the image of a crow and raven, which have developed in Lithuanian and Slavic phraseology and ethnic culture, are based on such characteristics as: black feathers, predatory behaviour, an unpleasant voice (the cry is mythologized, and it is associated with misfortunes and death). The image of the crow is often ironic and comical, while the image of the raven is much more negative. The crow is a cultural symbol of foolishness, while the raven is associated with wisdom. However, both Lithuanian and Slavic phraseology have their own peculiar images of the crow and the raven.